Blunt traumatic rupture of the thoracic oesophagus. Issue 10 (October 1988) - Young, C P; Large, S R; Edmondson, S J
Abstract : A man with a crush injury of his upper abdomen developed bilateral pulmonary empyema after repair of tears of the oesophagus and liver. Attempts to withdraw chest drains led to recurrent septicaemia, treated by reinsertion of the drains plus administration of antibiotics. The communication of the empyema space with both the bronchial tree and the oesophagus was managed successfully with intermittent positive pressure ventilation and with a double lumen endobronchial tube isolating the right lung for 10 days. Traumatic rupture of the thoracic oesophagus carries a high mortality and prompt repair is vital.